PENERAPAN TERAPI RELAKSASI GENGGAM JARI TERHADAP PENINGKATAN PERFUSI PERIFER PADA PENDERITA HIPERTENSI - Prissilla, Tasyha; Alfianur; Saputra, Candra; Erlin, Fitry (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: to identify description of the results of the practice of the Nursing Profession with the Application of Gerontic Nursing Care with the Application of Finger-Grasping Relaxation Therapy to Increase Peripheral Perfusion in Hypertension Patients. Methods: This article the method used in the implementation of nursing interventions is the provision of Finger Grasp Relaxation therapy in elderly people with hypertension. The implementation was carried out for 7 consecutive days for 10 minutes. The subjects in this application were 2 elderly people. Results: The results of this case study after 7 days of subjects applying finger grip relaxation therapy showed that on average after being given there was a significant difference in the success of the elderly in the recommended activities before and after being given finger grip relaxation and there was a change in systolic and diastolic blood pressure in the elderly with hypertension. Conclusion: The advantage of this finger holding relaxation therapy is that it balances the energy in the body to control emotions which allows the body to relax